Vitamin B12 and omega-3 fatty acids together regulate lipid metabolism in Wistar rats. (August 2015) - Khaire, Amrita; Rathod, Richa; Kale, Anvita; Joshi, Sadhana
Abstract: Our recent study indicates that maternal vitamin B12 and omega-3 fatty acid status influence plasma and erythrocyte fatty acid profile in dams. The present study examines the effects of prenatal and postnatal vitamin B12 and omega-3 fatty acid status on lipid metabolism in the offspring. Pregnant dams were divided into five groups: Control; Vitamin B12 deficient (BD); Vitamin B12 supplemented (BS); Vitamin B12 deficient group supplemented with omega-3 fatty acids (BDO); Vitamin B12 supplemented group with omega-3 fatty acids (BSO). The offspring were continued on the same diets till 3 month of age. Vitamin B12 deficiency increased cholesterol levels ( p <0.01) but reduced docosahexaenoic acid (DHA) ( p <0.05), liver mRNA levels of acetyl CoA carboxylase-1 (ACC-1) ( p <0.05) and carnitine palmitoyltransferase-1 (CPT-1) ( p <0.01) in the offspring. Omega-3 fatty acid supplementation to this group normalized cholesterol but not mRNA levels of ACC-1 and CPT-1. Vitamin B12 supplementation normalized the levels cholesterol to that of control but increased plasma triglyceride ( p <0.01) and reduced liver mRNA levels of adiponectin, ACC-1, and CPT-1 ( p <0.01 for all). Supplementation of both vitamin B12 and omega-3 fatty acid normalized triglyceride and mRNA levels of all the above genes. Prenatal and postnatal vitamin B12 and omega-3 fatty acids together play a crucial role in regulating the genes involved in lipid metabolism in adult offspring.